2017
DOI: 10.1111/nyas.13445
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and prepubertal body size predict menarcheal age in India, Peru, and Vietnam

Abstract: Evidence on the associations of birth weight and prepubertal nutritional status with menarcheal age for low-and middle-income countries is limited. We investigated these relationships using the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
(230 reference statements)
0
16
0
Order By: Relevance
“…The relationships between nutritional status and menarcheal ages are complex and are influenced by biological and environmental factors (Aurino et al, ; Juul, Chang, Brar, & Parekh, ; Pathak, Tripathi, & Subramanian, ; Soliman, De Sanctis, & Elalaily, ). Whereas genetics are primary determinants, menarcheal ages are also associated positively with maternal well‐being, breastfeeding rates, certain diseases (e.g., diabetes), and negatively with intake of animal proteins, psychological stress, standard of living, and environmental exposure to endocrine disruptors (Abreu & Kaiser, ; Aurino et al, ; Yermachenko & Dvornyk, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationships between nutritional status and menarcheal ages are complex and are influenced by biological and environmental factors (Aurino et al, ; Juul, Chang, Brar, & Parekh, ; Pathak, Tripathi, & Subramanian, ; Soliman, De Sanctis, & Elalaily, ). Whereas genetics are primary determinants, menarcheal ages are also associated positively with maternal well‐being, breastfeeding rates, certain diseases (e.g., diabetes), and negatively with intake of animal proteins, psychological stress, standard of living, and environmental exposure to endocrine disruptors (Abreu & Kaiser, ; Aurino et al, ; Yermachenko & Dvornyk, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between nutritional status and menarcheal ages are complex and are influenced by biological and environmental factors (Aurino et al, ; Juul, Chang, Brar, & Parekh, ; Pathak, Tripathi, & Subramanian, ; Soliman, De Sanctis, & Elalaily, ). Whereas genetics are primary determinants, menarcheal ages are also associated positively with maternal well‐being, breastfeeding rates, certain diseases (e.g., diabetes), and negatively with intake of animal proteins, psychological stress, standard of living, and environmental exposure to endocrine disruptors (Abreu & Kaiser, ; Aurino et al, ; Yermachenko & Dvornyk, ). Among anthropometric indicators, lower birthweights and higher prepubertal body masses have been linked with earlier menarche (Adair, ; Aurino et al, ; Blell, Pollard, & Pearce, ; Cooper, Kuh, Egger, Wadsworth, & Barker, ; Hui, Leung, Wong, Lam, & Schooling, ; Khan et al, ; Leenstra et al, ; Marcovecchio & Chiarelli, ; Persson et al, ; Simondon et al, ; Sloboda, Hart, Doherty, Pennell, & Hickey, ; Tam, de Zegher, Garnett, Baur, & Cowell, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has suggested that production of certain hormones, such as leptin, may send this message triggering menarche, possibly accelerating pubertal onset for overweight/obese girls . Previous studies have identified relationships between obesity and early sexual maturation, further bolstering this view . It is not surprising, then, that overweight/obesity may be associated with early pubertal onset.…”
Section: Discussionmentioning
confidence: 99%